Explaining the under-performance of the anti-human-trafficking campaign: experience from the United States and Europe - McDonald, William Frank (Crime, law and social change, 2014)
The American and the global campaigns against the trafficking of humans for labor and for sexual exploitation have had more than a decade of time and millions of dollars of support in an effort to suppress trafficking and protect its victims. Four of the six articles in this issue explore the reasons why the campaign in the United States has not had more instrumental success with respect to its prosecution goals. The number of cases brought and convictions obtained are fewer than what might be expected. Most of the cases brought involve sex trafficking. The less than impressive record of enforcement against human trafficking appears to be another example of how even very popular law reforms and crusades can be cooled out by the social realities of the criminal justice system. Sex trafficking cases are difficult to make because the victims are difficult to work with, juries are unsympathetic, and the police, prosecutors, judges have their own priorities. The article on the attempt to eliminate sex trafficking by switching to a policy of regulating prostitution rather than treating it as a crime indicates that policy change did not succeed. An attempt to create an index for assessing the implementation of anti-trafficking programs was successful.